2021
DOI: 10.1088/1742-6596/1910/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Sale Forecasting Based on SVR Integrated Promotion Factors

Abstract: In order to improve the inventory management level of pharmaceutical chain enterprise, drug sales forecasting is needed. Using machine learning SVR model, we forecast the drugs sale amount with a relatively high accuracy. Suppose the sales amount is influenced by promotion strategy, we integrated the promotion factors into the SVR model. Experimental result of drug sales prediction on the real sales data of a large chain drug company S shows that the SVR algorithm integrated with promotion factors get the accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Zhan et al [11] developed a Bayesian linear regression method to predict product sales and found that this method performed well in terms of MAE and RMSE. Liu et al [12] designed a support vector regression model to predict drug sales and improve inventory management, achieving an accuracy rate of 91% for this method.…”
Section: Introductionmentioning
confidence: 99%
“…Zhan et al [11] developed a Bayesian linear regression method to predict product sales and found that this method performed well in terms of MAE and RMSE. Liu et al [12] designed a support vector regression model to predict drug sales and improve inventory management, achieving an accuracy rate of 91% for this method.…”
Section: Introductionmentioning
confidence: 99%